Improving Quality and Productivity through Human Resource Development of Fish Processing Groups in Sinjai Regency - Mochamat Nurdin; Syamsiah Hasyim (Tinta Emas Institute, 2025)
This study aims to analyze the quality and productivity of human resource development (HRD) in fish processing groups in Sinjai Regency, South Sulawesi. The research focused on the effectiveness of training conducted by the Fisheries Office and the Cooperatives, SMEs, and Manpower Office in increasing the capacity of business groups. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that the training provided was not fully optimal, primarily due to a weak needs assessment before the program was implemented. The fish smoking group, despite having a high production of up to 1,400 kg in 2016, had not received specific training tailored to their needs. As a result, training tended to be a program formality without having a significant impact on improving the group's skills or productivity. Comparative analysis with previous research confirms the finding that training effectiveness is strongly influenced by the relevance of the material, participant participation, and the active role of extension workers in the learning process. The achievement rate of training targets in the 2021–2023 period was also relatively low, only around 30–40% of the 50% target set annually. This indicates a gap between program planning and the actual needs of participants in the field. Therefore, a more adaptive development strategy is needed through needs assessments, increased group participation, and alignment of training materials with regional strengths to ensure more effective and sustainable human resource development.